INTRACELLULAR ENERGY DEFICIT AND CONNECTIVE TISSUE BREAKDOWN AS THE LEADING PATHOPHYSIOLOGICAL MECHANISM OF POSTRADIATION ENERGY-MATRIX DYSINTEGRATION - Vastyanov, R.S.; Talalayev, K.O.; Ostapenko І.О.; Hruzevskiy О.А.; Babienko, V.V.; Yatsyna, O.I. (World of Medicine and Biology, 2025)
The purpose of the study was to investigate the pathogenetic significance of the correlation between disturbances in the energy balance of connective and muscle tissue cells and changes in collagenolysis after γ-irradiation. Male sexually mature Wistar rats were exposed to ionizing radiation at doses of 1.0 Gy and 4.0 Gy. The content of total oxyproline and its fractions, total glycosaminoglycans, adenyl nucleotides, and alanine- and aspartate aminotransferase activity were determined in animals’ skin, blood, skeletal, and cardiac muscles. The data obtained indicated activation of collagen breakdown and structural destabilization of the matrix in response to γ-radiation. Both alanine- and aspartate aminotransferase activities decreased in muscle tissue, paralleled by decreased blood levels in these conditions, indicating membrane damage and enzyme release into the extracellular space. The post-radiation decrease in ATP concentration and the accumulation of ADP and AMP in cardiac and skeletal muscles outline the cellular energy deficit. The authors declare that γ-radiation initiates a complex, dose-dependent set of changes in the “energy metabolism – extracellular matrix” system, manifested by simultaneous disruption of collagen and mitochondrial metabolism, interpreted as post-radiation energy-matrix disintegration and considered a universal mechanism. The data obtained confirm the reasonability of the integral index of energy-matrix condition creation for early diagnosis of radiation-induced tissue damage.